Occupational accidents with exposure to biological material: Description of cases in Bahia - Santos Carneiro e Cordeiro, Tecia Maria; Carneiro Neto, Jose Nunes [UNESP]; Brandao Cardoso, Mariana de Castro; Santana Mattos, Amalia Ivine; Bernardes Santos, Kionna Oliveira; Araujo, Tania Maria de (Univ Santa Cruz Do Sul, 2016)
Background and Objectives: This study is included in the field of public health in Brazil, specifically in workers' health, as occupational accidents with exposure to biological material comprise a preventable injury. Therefore, the objective was to describe the risk factors related to occupational accidents with exposure to biological material and post-exposure adopted behaviors in cases reported in the Notifiable Disease Information System (SINAN) in the state of Bahia in 2012. Methods: This is a descriptive epidemiological study of data from SINAN disease notifications in February 2013, of which analysis was performed by descriptive statistics in absolute and relative frequencies. Results: The results indicate a higher incidence of occupational accidents with exposure to biological material in Bahia in the female population (78.1%) aged between 30-49 years (51.5%); blood was the fluid involved in most accidents, 75.2% by percutaneous route (71.5%); post-exposure procedures were adopted according to the recommendations of the Ministry of Health; several pieces of information were missing from the notifications and only 23.8% of Occupational Accident Communication (OAC) notification forms were issued. Conclusion: It is necessary to create strategies on occupational health and safety awareness among workers about the relevance of the measures adopted after occupational accidents with exposure to biological material and the training of professionals for the reporting of cases and investigation, filling out all fields in the notification form and also the issuance of the OAC.
Keywords: Occupational exposure; Risk factors; Occupational accidents registry; Accidents; occupational; Occupational health